2019
DOI: 10.1101/512798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil Bacterial and Fungal Response to Wildfires in the Canadian Boreal Forest Across a Burn Severity Gradient

Abstract: Global fire regimes are changing, with increases in wildfire frequency and severity expected for many North American forests over the next 100 years. Fires can result in dramatic changes to C stocks and can restructure plant and microbial communities, which can have long-lasting effects on ecosystem functions. We investigated wildfire effects on soil microbial communities (bacteria and fungi) in an extreme fire season in the northwestern Canadian boreal forest, using field surveys, remote sensing, and high-thr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
(113 reference statements)
0
7
1
Order By: Relevance
“…Peatlands in late spring/early summer SRI versus LRI fire had relatively similar depth of peat layer (Figure 2), while peat depths in transitional areas were significantly greater following SRI fire (Figure 2). These results were contrary to Whitman et al (2019), who found that peat depths were greater in LRI fires compared with SRI fires that occurred in summer in both boreal forests and peatlands. Differences may be due to enhanced drying and disconnection from regional groundwater following evaporative drying in summer in peatlands that had not been burned in recent decades, compared with shallower depth to water table in peatlands that had burned recently (e.g., Kettridge et al, 2014).…”
Section: Soil Characteristics Of Sri and Lri Fire In Western Boreal P...contrasting
confidence: 99%
See 1 more Smart Citation
“…Peatlands in late spring/early summer SRI versus LRI fire had relatively similar depth of peat layer (Figure 2), while peat depths in transitional areas were significantly greater following SRI fire (Figure 2). These results were contrary to Whitman et al (2019), who found that peat depths were greater in LRI fires compared with SRI fires that occurred in summer in both boreal forests and peatlands. Differences may be due to enhanced drying and disconnection from regional groundwater following evaporative drying in summer in peatlands that had not been burned in recent decades, compared with shallower depth to water table in peatlands that had burned recently (e.g., Kettridge et al, 2014).…”
Section: Soil Characteristics Of Sri and Lri Fire In Western Boreal P...contrasting
confidence: 99%
“…Boreal peatlands are composed of thick layers of insulating moss vegetation, which extend to depths greater than 0.4 m due to gradual processes of carbon sequestration, biomass accumulation and slow rates of decomposition (Benscoter et al, 2011;Kuhry, 1994). The largely moist characteristics of peatlands make them an important refuge from wildland fire, increasing the years between fire compared with surrounding upland forests (Turetsky et al, 2004;Whitman et al, 2019;Zoltai et al, 1998). The period between fires is described as a 'fire return interval'.…”
Section: Introductionmentioning
confidence: 99%
“…A fire resilience index could also be developed for systems where crown-killing fire is the common fire regime, but would need to incorporate the variation in regeneration methods and optimal fire return intervals (Enright et al, 2015). In general, fire-embracing species possessing either serotiny or resprouting ability are resilient to stand-replacing, high-severity fire, although with ongoing anthropogenic and climate-driven shortening of fire return intervals in such crown-fire-adapted ecosystems, these species are also at risk of population declines (Enright et al, 2015;Turner, Braziunas, Hansen, & Harvey, 2019;Whitman, Parisien, Thompson, & Flannigan, 2019). Furthermore, fire-avoiding species (Keeley, 2012) may also be resilient to stand-replacing fire if tree establishment proceeds during sufficiently long fire-free intervals and if post-fire spatial mosaics of live tree refugia are complex enough for seed dispersal to initiate forest succession.…”
Section: Discussionmentioning
confidence: 99%
“…Aspen and birch are also replacing black spruce after severe fires, and the fate of postfire deciduous forest will almost certainly be determined by similar abiotic and biotic drivers to those studied here. In other parts of the North American boreal biome, lodgepole pine and jack pine trees are now becoming dominant over black spruce after fire (Jean, Pinno, & Nielsen, 2020;Johnstone & Chapin, 2003;Searle & Chen, 2017;Whitman, Parisien, Thompson, & Flannigan, 2018;Whitman et al, 2019). We must evaluate whether and how feedbacks will form that determine the long-term fate of these emerging vegetation types.…”
Section: Gaining Mechanistic Insights Across the North American Bormentioning
confidence: 99%